Autologous Adipose Stem Cells in Treatment of Female Stress Urinary Incontinence: Results of a Pilot Study. (1st July 2014) - Kuismanen, Kirsi; Sartoneva, Reetta; Haimi, Suvi; Mannerström, Bettina; Tomás, Eija; Miettinen, Susanna; Nieminen, Kari
Abstract : The purpose of the study was to find out whether transurethral injections of autologous adipose stem cells (ASCs) are an effective and a safe treatment for female stress urinary incontinence (SUI). Validated questionnaires showed some subjective improvement in all patients. Thus far, the treatment with autologous ASCs has proven safe and well tolerated, but additional research is needed to develop SUI injection therapies. Abstract: The purpose of our study was to find out whether transurethral injections of autologous adipose stem cells (ASCs) are an effective and a safe treatment for female stress urinary incontinence (SUI). We treated five SUI patients with ASCs combined with bovine collagen gel and saline. Prior to the treatment, the ASCs were isolated from subcutaneous fat and expanded for 3 weeks in a good manufacturing practice-level laboratory. The mixture of ASCs and collagen was injected transurethrally via cystoscope. Additionally, viability, multipotency, and surface marker profile of ASCs were analyzed in vitro. We followed up with patients 3, 6, and 12 months after the injections. The primary endpoint was a cough test to measure objectively the effect of the treatment. Validated questionnaires were used to determine the subjective cure rate. After 6 months, 1 of 5 patients displayed a negative cough test with full bladder filled with 500 ml of saline. At 1 year, the cough test was negative with three patients; two of them were satisfied with the treatment and did not wish further treatment for SUI. Validated questionnaires showed some subjective improvement in all five patients. This is the first study describing the use of autologous ASCs in combination with collagen gel for female SUI treatments. Thus far, the treatment with autologous ASCs has proven safe and well tolerated. However, the feasibility and efficacy of the treatment were not optimal; therefore, additional research is needed to develop SUI injection therapies.